(3QSGdI GdEaUGM HHYV eG LGA ef GdNWC aj GdEjVGMs - (3CHhGdMSjf SdjeGf Hf eMeO Hf YHO Gddg GdSHGFj GdeGdbj, GdeYQha H` GHf GdWQGhIs; (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSj, CHh Ydj,J (B377 (3g` s
(3ChdgG (B:s
(3NUge GdCSJGP GdChMO GHf GdWQGhI Hecfhf HMKg, hCKQge Ydi GdLedI ef CYjGf hbJg s
(3BNQgG (B:s
(3hdh JcdafG GdhaGA Hcd eG LQi ajg ef NWC hJbUjQ dGeJO GdcdGe, hNQLJ GdQSGdI Yf HZjJgG ef GdEjLGR hHGddg fSJYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3hWjGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B128 s
Keywords: (3GdfMhs